Identification of a Sulfatase that Detoxifies Glucosinolates in the Phloem-Feeding Insect Bemisia tabaci and Prefers Indolic Glucosinolates - Manivannan, Abinaya; Israni, Bhawana; Luck, Katrin; Götz, Monika; Seibel, Elena; Easson, Michael L. A. E.; Kirsch, Roy; Reichelt, Michael; Stein, Beate; Winter, Stephan; Gershenzon, Jonathan; Vassão, Daniel Giddings (Frontiers in Plant Science, 2021)
Cruciferous plants in the order Brassicales defend themselves from herbivory using glucosinolates: sulfur-containing pro-toxic metabolites that are activated by hydrolysis to form compounds such as isothiocyanates, which are toxic to insects and other organisms. Some herbivores are known to circumvent glucosinolate activation with glucosinolate sulfatases (GSS), enzymes that convert glucosinolates into inactive desulfoglucosinolates. This strategy is a major glucosinolate detoxification pathway in a phloem-feeding insect, the silverleaf whitefly Bemisia tabaci, a serious agricultural pest of cruciferous vegetables. In this study, we identified and characterized an enzyme responsible for glucosinolate desulfation in the globally distributed B. tabaci species MEAM1. In in vitro assays, this sulfatase showed a clear preference for indolic glucosinolates compared to aliphatic glucosinolates, consistent with the greater representation of desulfated indolic glucosinolates in the honeydew. B. tabaci might use this detoxification strategy specifically against indolic glucosinolates since plants may preferentially deploy indolic glucosinolates against phloem-feeding insects. In vivo silencing of the expression of the B. tabaci glucosinolate sulfatase gene via RNA interference led to lower levels of desulfoglucosinolates in the honeydew. Our findings expand the knowledge on the biochemistry of glucosinolate detoxification in phloem-feeding insects, and suggest how detoxification pathways might facilitate plant colonization in a generalist herbivore.